2017
DOI: 10.1093/jscr/rjx153
|View full text |Cite
|
Sign up to set email alerts
|

Non-curative surgery for aortoenteric fistula

Abstract: Graft infection with secondary aortic fistula is a rare complication following implantation of aortic prostheses, frequently occurring after emergency procedures and reoperations. The condition is associated with considerable morbidity and mortality. Curative treatment consists of explantation of the infected graft followed by fistula revision and implantation of a new graft in combination with antimicrobial therapy. Non-curative treatment with aortic stentgraft and long-term substitution treatment with antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…In the first phase, resuscitation and haemodynamic support are of priority. Preoperative intravenous broad-spectrum antibiotic therapy for Gram+, Gram–, and enteric pathogens may be administrated followed by targeted therapy [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the first phase, resuscitation and haemodynamic support are of priority. Preoperative intravenous broad-spectrum antibiotic therapy for Gram+, Gram–, and enteric pathogens may be administrated followed by targeted therapy [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the importance of establishing the underlying mechanism of fistula formation, their etiology remains unclear. It has been suggested that either chronic infection of the graft or physical stimulation, such as from aortic pulsation pressure, contributes to their formation, which is usually determined based solely on the clinical course or surgical findings [ 12 – 19 ]. To the best of our knowledge, only 25 case reports on SAEFs have been published (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] 85 M Melena, tiredness, dizziness, fever EVAR 2 yr 4 m Aortic reconstruction, bowel repair, debridement Alive at 15 months Unclear 24 2017 Hansen et al . [ 12 ] 75 F Melena Open surgery 2 yr Open surgery + EVAR Alive at 12 years Infection 25 1998 Yabu et al . [ 25 ] 77 M Dyspnea Open surgery 10 yr None * Died + Mechanical factor EVAR endovascular aortic reconstruction, F female, m month, M male, SAEF secondary aortoenteric fistula, yr year †period after abdominal aortic aneurysm treatment ‡whether pathological examination was performed or not §possible cause suggested by authors of the report *patient died immediately before any treatment …”
Section: Discussionmentioning
confidence: 99%
“…Recently, small case series and case reports have been published describing the results of the treatment of infected endografts without explantation. 5,6 Although long-term results are lacking, some evidence seems to support this modality in highly selected patients who would not benefit from the invasive gold standard of the removal of all infected materials. As such, the patient described here would traditionally be treated by graft explantation and aortic revascularization by an aggressive surgeon or referred to hospice care by a conservative one.…”
Section: Discussionmentioning
confidence: 99%